Soft Tissue Sarcoma – a Current Review of the Diagnostic and Treatment Strategies - Scheidt, Sebastian; Jacobs, Cornelius; Koob, Sebastian; Welle, Kristian; Walter, Sebastian; Jakob, Jens; Kehrer, Michael; Schmolders, Jan (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Soft tissue sarcomas are a heterogeneous group of neoplasias that due to their often clinically silent appearance often remain undetected or experience delayed treatment. Especially soft tissue swelling is often misinterpreted by patients and doctors and trivialized or verified with an incorrect biopsy technique. The hereby evoked complications for the patients are serious and may be reduced by simply following the available guidelines. The treatment of soft tissue sarcomas requires a close interdisciplinary coordination between specialists in tumor orthopedics, oncology, radiology, pathology and radiotherapy. On the basis of a selective literature review, the following article points out the current evidence on the treatment and illustrates a treatment algorithm.
Keywords: soft tissue sarcoma; tumor orthopedics; treatment algorithm; guidelines; review